The Role of P53 Serine 46, Burkitt Cell Lymphoma 2 (BCL-2), and Cysteinyl Aspartate Specific Proteinase 3 (Caspase 3) Proteins as Risk Factors in Abortion (Medico Legal Update, 2021)
An Incomplete abortion is one of the complications that often occur during pregnancy, but the biomolecularmechanism is still unknown. It has proven to be an increase in apoptosis activity that is controlled by avariety of proteins, including p53 Ser 46, Bcl-2, and caspase 3, in uteroplasenta and reproductive organs. Theaim of the study is to measure the level of protein p54 Ser 46, Bcl-2, and caspase 3 in abortion and normalpregnancy. A case control study conducted in 38 cases of incomplete abortion and 38 normal pregnancies asa control. The level of protein of Ser 46, Bcl-2, and caspase 3 examined by ELISA independent/Duplo. Thehigher level of p53 Ser 46 (> 0,09 U/mL) led to higher risks of abortion with OR 8.52; 95% CI, 2.65 to 28.6.The higher level of Bcl-2 led to higher risks of abortion with OR 3.75; 95% CI, 1.24 to 11.68. The higherlevel of caspase 3 (> 7 mg/mL) and p53 Ser 46 (> 0,09 U/mL) led to higher risks of abortion with OR 71.15;95% CI, 8.74 to 578.92; with the result of series p, p, 0.001; p < 0.008; and p = 0.001. Level of protein p53Ser 46 and caspase 3 in abortion is higher than normal pregnancies, while the Bcl-2 protein levels in abortionis lower than normal pregnancies.